Do Gender Conformity Pressure and Occupational Knowledge Influence Stereotypical Occupation Preferences in Middle Childhood? - Masters, Stephanie; Barth, Joan (Frontiers in Education, 2022)
This study investigates how perceived occupational knowledge, gender stereotypes, and pressure to conform to gender norms influence children’s career interests in a sample of fourth and fifth grade children (N = 178, Mage = 9.78 years, 46.6% girls). Children were interested in and perceived that they knew more about own gender dominated occupations, compared to other gender dominated occupations. Gender moderated the effect of gender conformity pressure and gender stereotypes on interest in female-dominated but not male-dominated occupations. Boys were less interested in female-dominated occupations when they felt pressure to conform to gender norms and held more stereotypical beliefs about those occupations. These results suggest that perceived occupational knowledge is an important, yet overlooked, factor in understanding gender differences in children’s occupational interests.